Evaluation Model of Environmental Sustainable Competitive Tourism Based on Entropy - Pantović, Danijela; Kostić, Marija; Veljović, Sonja; Luković , Milica (Problemy Ekorozwoju, 2023)
Despite the valuable economic benefits of tourism, it must be highlighted that the tourism industry is an important source of stress for the environment with the main influence on tourist destinations. The aim of this study is to investigate the elements of environmental sustainability in tourism as key factors in the competitiveness of tourism using entropy methods. According to the authors’ knowledge, it is the first time that the entropy model applied to Environmental sustainability indicators, regarding entropy as a measure of non-uniformity among sustainability indicators of EU countries. The data of the EU were used and Environmental sustainability pillar of the Travel & Tourism Competitiveness Index. The results show that the total entropy of the competitiveness of tourism within the environmental sustainability sub-index of the EU countries speaks in favor of the uniformity of the indicators. The study also reveals significant differences among the EU27 in the domain of the Global Climate Risk index, Baseline water stress and Forest cover loss. Furthermore, convergence has been achieved so far in the indicators Red List Index and Environmental treaty ratification. Finally, the methodological approach of this study has the potential to be extrapolated worldwide, especially in the future era of global environmental problems.